2015
DOI: 10.1016/j.proche.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Lactic Acid Using Microwave and Conventional Heating

Abstract: The polymerization of lactic acid (LA) has been investigated by two methods: conventional heating and under microwave irradiation. The reactions of polymerization have been carried out in two stages: at the beginning water is removed and oligomer is obtained; then, the catalysts/co-catalysts are added and reactions are carried out. Tin octoate, toluene sulfonic acid, 2-aminopropanoic acid (alanine) have been investigated as polymerization catalysts and the derivatives of 2,4,6,8- tetramethilol -2,4,6,8- tetraa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…El Knidri, El Khalfaouy, Laajeb, Addaou, and Lahsini (2016) and Sebastian, Rouissi, Brar, Hegde, and Verma (2019) reported the extraction of chitosan and chitin from, respectively, shrimp shell waste and fungal biomass using MW irradiation with huge reduction in extraction time and high degree of deacetylation in few minutes. It has been reported that the MW‐assisted polymerization process of lactic acid to produce PLA is 100 times faster than the convention heating method (Bakibaev et al., 2015; Singla, Mehta, Berek, & Upadhyay, 2014). However, the MW radiation did not cause any significant improvement in the mechanical, thermal, and optical properties of PLA.…”
Section: Coupling Innovative Food Processing Technologies and Packagimentioning
confidence: 99%
“…El Knidri, El Khalfaouy, Laajeb, Addaou, and Lahsini (2016) and Sebastian, Rouissi, Brar, Hegde, and Verma (2019) reported the extraction of chitosan and chitin from, respectively, shrimp shell waste and fungal biomass using MW irradiation with huge reduction in extraction time and high degree of deacetylation in few minutes. It has been reported that the MW‐assisted polymerization process of lactic acid to produce PLA is 100 times faster than the convention heating method (Bakibaev et al., 2015; Singla, Mehta, Berek, & Upadhyay, 2014). However, the MW radiation did not cause any significant improvement in the mechanical, thermal, and optical properties of PLA.…”
Section: Coupling Innovative Food Processing Technologies and Packagimentioning
confidence: 99%
“…Among these advantages, shortening drastically the times of heating is an important gain in polymer processing at industrial scale. For example, solvent-free synthesis of poly(lactic acid), by polymerization of lactic acid, in the presence of tin octoate and isoamyl alcohol, is carried out in 16 hours when conventional heating is used, against only 10 minutes under microwave heating [26] (reaction time is about hundred times shorter). Giguere et al [27] published a comparison of reaction times between the two modes for many reactions such as Diels-Alder and ene reactions, and they noticed very important decreases when microwaves were used from a few hours to a few minutes.…”
Section: Benefits Of Microwave Heating Compared Tomentioning
confidence: 99%
“…Sn(Oct) 2 was selected due to its wide use as a catalyst in esterification processes, 16,17 and the significant number of previous studies involving its use in MWH reactions. [21][22][23][24] DHBTC was selected as its primary use has also been in step-growth polyesterification systems, 25,26 and because it exhibits a different state at room temperature (RT) than Sn(Oct) 2 . The former catalyst is liquid at RT, the latter is a solid.…”
Section: Introductionmentioning
confidence: 99%